Identification of AREG and PLK1 pathway modulation as a potential key of the response of intracranial 9L tumor to microbeam radiation therapy. Issue 11 (11th December 2014) - Bouchet, Audrey; Sakakini, Nathalie; Atifi, Michèle El; Le Clec'h, Céline; Bräuer‐Krisch, Elke; Rogalev, Léonid; Laissue, Jean Albert; Rihet, Pascal; Le Duc, Géraldine; Pelletier, Laurent
<x xml:space="preserve">Abstract</x> Synchrotron microbeam radiation therapy (MRT) relies on the spatial fractionation of a synchrotron beam into parallel micron‐wide beams allowing deposition of hectogray doses. MRT controls the intracranial tumor growth in rodent models while sparing normal brain tissues. Our aim was to identify the early biological processes underlying the differential effect of MRT on tumor and normal brain tissues. The expression of 28, 000 transcripts was tested by microarray 6 hr after unidirectional MRT (400 Gy, 50 µm‐wide microbeams, 200 µm spacing). The specific response of tumor tissues to MRT consisted in the significant transcriptomic modulation of 431 probesets (316 genes). Among them, 30 were not detected in normal brain tissues, neither before nor after MRT. Areg, Trib3 and Nppb were down‐regulated, whereas all others were up‐regulated. Twenty‐two had similar expression profiles during the 2 weeks observed after MRT, including Ccnb1, Cdc20, Pttg1 and Plk1 related to the mitotic role of the Polo‐like kinase (Plk) pathway. The up‐regulation of Areg expression may indicate the emergence of survival processes in tumor cells triggered by the irradiation; while the modulation of the "mitotic role of Plk1" pathway, which relates to cytokinetic features of the tumor observed histologically after MRT, may partially explain the control of tumor growth by MRT. The identification of these tumor‐specific responses permit to consider new strategies that might potentiate the antitumoral effect of MRT.